Morphological peculiarities of uterine tubes of fetuses from mothers with physiological pregnancy - L. S. Kupriyanovа (Zaporozhye State Medical University, 2014)
Aim. In order to identify the structural features of the fallopian tubes in fetuses from women with physiological pregnancy at different stages of gestation, the structure of 47 antenatally dead fetuses were investigated. Methods and results. Used such methods: anthropometric, organometric, histological, histochemical, morphometric and statistical. It has been established that in fetuses of 21st-28th weeks of gestation fallopian tubes are structurally completely formed, and at later dates the formation of their functional activity is noted. Conclusion. This suggests that the effect of mother's pathology in early pregnancy leads to more serious violations of the structure of the fallopian tubes of the fetus. Described morphological features of the structure of the fallopian tubes of fetuses from mothers with physiological pregnancy according to gestational age can be used as a control group of observations in the study of structure of the organs of fetuses from mothers with complicated pregnancy.